The sudden transition to synchronized online learning during the COVID-19 pandemic in Saudi Arabia: a qualitative study exploring medical students’ perspectives - Rehana Khalil (BMC Medical Education, 2020)
Abstract Background The closure of educational activities in the Kingdom of Saudi Arabia due to the ongoing COVID-19 pandemic resulted in an unplanned shift from traditional learning to a setup that exclusively involves digital teaching and learning. Within this context, the present study aimed to explore undergraduate medical students’ perceptions regarding the effectiveness of synchronized online learning at Unaizah College of Medicine and Medical Sciences, Qassim University, Saudi Arabia. Methods A qualitative study was conducted using virtual focus group discussions synchronously with the help of a discussion guide consisting of seven open-ended questions. Overall, 60 medical students were recruited using a maximum variation sampling technique; these students then participated in eight focus group discussions. All interviews were recorded, transcribed verbatim, and analyzed for thematic contents using the standard (Mayring, Kiger. M. E. and Braun.V) content analysis framework. Results A thematic content analysis yielded four core themes: (1) educational impact, (2) time management, (3) challenges encountered, and (4) preferences for the future. The online modality was well-received, and all participants agreed that online sessions were time saving and that their performance was improved due to enhanced utility of time; however, they indicated that they encountered some challenges, including methodological, content perception, technical, and behavioral challenges during sessions and online exams. Most of the preclinical students preferred online learning for the upcoming academic years. Conclusion Synchronized online classes were well-accepted by the medical students. This represents significant and promising potential for the future of medical education. The principles of the online learning model and learning outcomes should be rigorously and regularly evaluated to monitor its effectiveness.